2016
DOI: 10.4314/sajas.v47i2.11
|View full text |Cite
|
Sign up to set email alerts
|

Effects of initial fattening age on carcass characteristics and meat quality in Simmental bulls imported from Austria to Turkey

Abstract: The aim of this study was to determine the effects of initial fattening age on carcass and meat quality of Simmental bulls imported from Austria to Turkey. These animals were allocated to two initial ages of fattening groups, namely young (n = 74) and old group (n = 61) at 5.5 and 7.5 months old, respectively. After reaching the target final weights, the animals were slaughtered and the carcass characteristics, area and circumference of the longissimus thoracis et lumborum (LTL) muscle, marbling score, and mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
2
3
1
Order By: Relevance
“…A possible explanation for these results may be related to fatness, since the proportion of fat in carcasses increases and the relative proportion of muscles decreases, as animals become older. 13,14 These findings are consistent, in part, with those reported by Litwinczuk et al 15 who suggested that dressing percentage in heifers was higher com-…”
Section: Resultssupporting
confidence: 86%
“…A possible explanation for these results may be related to fatness, since the proportion of fat in carcasses increases and the relative proportion of muscles decreases, as animals become older. 13,14 These findings are consistent, in part, with those reported by Litwinczuk et al 15 who suggested that dressing percentage in heifers was higher com-…”
Section: Resultssupporting
confidence: 86%
“…At age <3 years mean sensory juiciness of Borana cattle was higher (P < 0.05) than Arsi. The mean juiciness value of Arsi (7 -9 years) was similar to mean (6.23 ± 0.21) reported for Dajal males cattle [34]. At age <3 years mean sensory Open Journal of Animal Sciences tenderness of Borana was significance different (P < 0.05) from Arsi.…”
Section: Resultssupporting
confidence: 77%
“…Younger cull cows and cows fed higher straw levels had heavier carcass that could be justified by their higher final BW. A recent study reported that the proportion of fat in carcasses increased, and the relative proportion of muscles decreased as animals become older [34]. However, fat percentage in carcass was similar between age groups in the current study.…”
Section: Discussioncontrasting
confidence: 44%